2018
DOI: 10.1021/acs.orglett.8b02066
|View full text |Cite
|
Sign up to set email alerts
|

Trisulfur Radical Anion (S3•–) Involved [1 + 2 + 2] and [1 + 3 + 1] Cycloaddition with Aromatic Alkynes: Synthesis of Tetraphenylthiophene and 2-Benzylidenetetrahydrothiophene Derivatives

Abstract: S-mediated [1 + 2 + 2] and [1 + 3 + 1] cycloaddition reactions of aromatic alkynes to give tetraphenylthiophene and 2-benzylidenetetrahydrothiophene derivatives via two C-S bond formations are developed. These two protocols provide new, simple, and straightforward strategies to construct tetraphenylthiophene and 2-benzylidenetetrahydrothiophene derivatives under transition-metal-free conditions. This study also expands the application of S in organic reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 27 publications
2
32
0
Order By: Relevance
“…On the other hand, a radical-based mechanism could be supported by a radical clock experiment in which a cyclopropane-derived substrate would deliver a ring- open product. 56,57 However, for the reaction of substrate 1r with a cyclopropyl substituent, we found that no ring-open product could be observed.…”
mentioning
confidence: 70%
“…On the other hand, a radical-based mechanism could be supported by a radical clock experiment in which a cyclopropane-derived substrate would deliver a ring- open product. 56,57 However, for the reaction of substrate 1r with a cyclopropyl substituent, we found that no ring-open product could be observed.…”
mentioning
confidence: 70%
“…Recently, Lei’s group reported the synthesis of 2,5-substituted thiophenes by means of [4+1] cycloaddition reactions of 1,3-diynes mediated by S 3 •– generated in situ from S 8 and a base . More recently, Ji’s group synthesized benzothiazine, thiophene, and 2-benzylidenetetrahydrothiophene derivatives by means of [5+1], [1+2+2], and [1+3+1] cycloaddition reactions involving S 3 •– generated in situ from K 2 S . However, cycloaddition reactions with a combination of K 2 S and S 8 as as the sources of sulfide have not been reported.…”
mentioning
confidence: 99%
“…In past literature reports, tetra-aryl thiophenes are obtained either by cyclization of the thiophene moiety or by substitutions on a thiophene backbone. Cyclization methods involve the lengthy synthesis of structurally complex starting materials and are not adapted for late-stage functionalization. Methods that involve stepwise arylations of a thiophene backbone are therefore more attractive, but face inherent challenges in the arylation of each position in a selective and controlled manner.…”
mentioning
confidence: 99%